2021
DOI: 10.1111/bcp.15005
|View full text |Cite
|
Sign up to set email alerts
|

Wound complications and bleeding with new oral anticoagulants in patients undergoing total joint arthroplasty: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aims The results of associations between new oral anticoagulants (NOACs) and wound complications after total joint arthroplasty remain inconsistent. We conducted a systematic review and meta‐analysis of randomized controlled trials to make comparisons with low molecular weight heparins (LMWH) on the clinical outcomes of total wound complications, together with other efficacy and safety endpoints to further evaluate the safety and efficacy of NOACs. Methods This meta‐analysis was conducted based on a published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Direct Thrombin Inhibitors: Direct thrombin inhibitors have also had inconsistent results in the literature. In a metaanalysis comparing dabigatran with LMWH and Factor Xa inhibitors, the authors found no difference with regard to wound complication rates 2105 . Gill et al, performed a prospective study comparing dabigatran and dalteparin, noting that the reoperation rate for wound complications in the dabigatran group was 7% compared to 1% in the dalteparin group 2106 .…”
Section: Jean-yves Jennymentioning
confidence: 98%
“…Direct Thrombin Inhibitors: Direct thrombin inhibitors have also had inconsistent results in the literature. In a metaanalysis comparing dabigatran with LMWH and Factor Xa inhibitors, the authors found no difference with regard to wound complication rates 2105 . Gill et al, performed a prospective study comparing dabigatran and dalteparin, noting that the reoperation rate for wound complications in the dabigatran group was 7% compared to 1% in the dalteparin group 2106 .…”
Section: Jean-yves Jennymentioning
confidence: 98%
“…Comparison of outcomes between FPX group and LMWH group before IPTW (A) and after IPTW (B). IPTW, inverse-probability-of-treatment weighting method a reduction in the risk of major/clinically relevant nonmajor bleeding events compared to LMWH [18].…”
Section: Table 1 (Continued)mentioning
confidence: 99%